What if you had animal eyes!? - Markle, Sandra; McWilliam, Howard, 1977- (2023)
"Explores what would happen if you looked in the mirror and saw a pair of animal eyes instead of your own. From the chameleon's eyes that can point in different directions, to the colossal squid's eyes that shine in the dark, discover what it would be like if you had these special eyes. Then, find out why your eyes are just the right ones for you"--
K-2nd Grade
Keywords: Eye -- Juvenile literature; Animals -- Juvenile literature; Eye; Animals; Eye; Animals; Animals; Eye; Juvenile works; Readers (Publications)